2021
DOI: 10.1145/3449216
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Entrepreneurial Activities in Marginalized Widows

Abstract: In some developing countries, widows are looked down upon and are often considered inauspicious especially in rural regions. Some societies even consider them and their issues invisible. This paper presents findings from a qualitative study focused on understanding how technology could facilitate entrepreneurial and DIY activities of widows from rural Sri Lanka. We conducted semi-structured interviews and field observations with thirteen widows from low socio-economic backgrounds, who were involved in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The current study shows that training aimed to improve entrepreneurial competence and economic self-efficacy is the surest way of empowering women farmers and widows. In addition, Rathnayake et al (2021) found that the use of modern technologies for entrepreneurial training could be useful in assisting widows in picking up the pieces of their lives. In the current study, we are more specific on the type of modern technology, visual multimedia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study shows that training aimed to improve entrepreneurial competence and economic self-efficacy is the surest way of empowering women farmers and widows. In addition, Rathnayake et al (2021) found that the use of modern technologies for entrepreneurial training could be useful in assisting widows in picking up the pieces of their lives. In the current study, we are more specific on the type of modern technology, visual multimedia.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers argue further that when widows are empowered through training, they will be better positioned to take care of their children. Rathnayake et al (2021) conducted a study to examine the impact of modern technologies in empowering widows in Sri Lanka. The researchers interviewed 13 women farmers who were widows and found that such women were marginalized because of the absence of their partners.…”
Section: Empowering Women Farmers Through Modern Technologiesmentioning
confidence: 99%
“…The emergence of hybrid entrepreneurship in Sri Lanka, despite the fact that this is not the case in many other countries, could be linked to the necessity of the current economic crisis. The situation as a developing economy, has caused people to reconsider their sources of income in order to meet their personal and family objectives and it is confronted with a number of issues that have resulted in poor living circumstances and poverty due to the COVID 19 pandemic and corruption of government [6]. Because of the high prevalence of lack of income and inflation in Sri Lanka as a whole, poverty has been seen as one of the countries features.…”
Section: Introductionmentioning
confidence: 99%